2004
DOI: 10.1007/bf03018493
|View full text |Cite
|
Sign up to set email alerts
|

Central dexmedetomidine attenuates cardiac dysfunction in a rodent model of intracranial hypertension

Abstract: The results demonstrate that dexmedetomidine attenuates cardiac dysfunction associated with ICH. Our results provide evidence for the role of central sympathetic hyperactivity in the development of cardiac dysfunction associated with ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Hall et al studied on model where intracranial hypertension was created to rodents, they injected intracisternal dexmedetomidine and observed that the left ventricular function was well protected and they thought this result was due to prevention of increased catecholamine release by dexmedetomidine which results in decreased free oxygen radical formation in heart tissue. In this study also the MDA levels in the dexmedetomidine group was lower than that in the control group [33]. In a recent study where the effect of dexmedetomidine was searched to decrease I/R injury due to tourniquet application for upper limb surgery, the MDA values in the dexmedetomidine group was significantly lower in respect to control group during the reperfusion phase [34].…”
Section: Discussionsupporting
confidence: 47%
“…Hall et al studied on model where intracranial hypertension was created to rodents, they injected intracisternal dexmedetomidine and observed that the left ventricular function was well protected and they thought this result was due to prevention of increased catecholamine release by dexmedetomidine which results in decreased free oxygen radical formation in heart tissue. In this study also the MDA levels in the dexmedetomidine group was lower than that in the control group [33]. In a recent study where the effect of dexmedetomidine was searched to decrease I/R injury due to tourniquet application for upper limb surgery, the MDA values in the dexmedetomidine group was significantly lower in respect to control group during the reperfusion phase [34].…”
Section: Discussionsupporting
confidence: 47%
“…Another possibility suggested is that by decreasing plasma catecholamines and tissue MDA in the heart, dexmedetomidine attenuates cardiac ischemia. 28 Dexmedetomidine is a lipophilic phenyl imidazole derivative with a higher affinity for ␣ 2 -adrenoceptors than that of the prototype drug clonidine. 29 Clonidine produces the membranotropic and membrano-stabilizing effects, which are associated with high lipophilic activity.…”
Section: Discussionmentioning
confidence: 99%
“…[22] have also shown that neonatal rats (7 days old) are more sensitive to dexmedetomidine than older pups (15-29 days old). Intracisternal administration of dexmedetomidine has prevented the rise of plasma norepinephrine, blocked the electrocardiographic abnormalities and preserved cardiac function in a rat model of intracranial hypertension [23]. Dexmedetomidine also exerts direct protective effect on left ventricular dysfunction caused by hypoxia-reoxygenation in rats [24] and decreases airway reactivity [25].…”
Section: Discussionmentioning
confidence: 99%